Človeški podobna umetna inteligenca in superinteligenca - Žalec, Bojan (Bogoslovni vestnik, 2024)
The author deals with the question of the probability of the emergence of humanlike artificial intelligence and the emergence of superintelligence. He argues that no emergence is probable. The probability of the first is rejected, following Erik J. Larson's argumentation based on the essential characteristics of human intelligence. These include generality, intuition, common sense, and abduction. The probability of the onset of superintelligence is rejected based on arguments provided by François Chollet, emphasizing the non-generality, situationality and contextuality, and externalism of intelligence. The author demonstrates the importance of a correct understanding of the concept of intelligence and its definition. Misunderstanding can have negative effects far beyond the academic realm, including unjustified financial gains and damage in terms of organizing scientific work (big science, hive science), and fostering conditions for creativity.
Keywords: abduction; abdukcija; Artificial Intelligence; big science; common sense; externalism of intelligence; generality; intuicija; intuition; particularity of intelligence; partikularnost inteligence; probability of humanlike artificial intelligence; probability of superintelligence; splošnost; umetna inteligenca; velika znanost; verjetnost človeški podobne umetne inteligence; verjetnost superinteligence; zdravi razum; zunanjostnost inteligence